PERANCANGAN REPOSITORY PENGETAHUAN TUMBUHAN OBAT BERBASIS ONTOLOGY MENGGUNAKAN PROTÉGÉ 4.3.0 - Azimah, Ariana; Jusuf, Heni (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2015)
Indonesia is a country that has biodiversity many benefits for human survival. One is the herbs that can be used as an herbal medicine. In the modern era of herbal medicine is still often taken as a first aid when someone is having health problems. Herbal medicine can be obtained by utilizing the natural surroundings of this .repository can usage information medicinal plants for health. In This paper discussed about the design of which will be carried out based ontology using protégé tools.generate a repository of medicinal plants that are useful to society